2012
DOI: 10.1134/s0021364012060021
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of superfluid 3He in “nematically ordered” aerogel

Abstract: Results of experiments with liquid 3 He immersed in a new type of aerogel are described. This aerogel consists of Al 2 O 3 ⋅ H 2 O strands which are nearly parallel to each other, so we call it as a "nematically ordered" aerogel. At all used pressures a superfluid transition was observed and a superfluid phase diagram was measured. Pos sible structures of the observed superfluid phases are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
(46 reference statements)
0
33
1
Order By: Relevance
“…They are just two of many p-wave states each distinguished by unique broken symmetries and these are the only stable states in pure 3 He in low magnetic field [1]. However, new phases in this manifold have been reported for superfluid confined within an anisotropic external framework; in one case chiral states within positively strained 98% porous, silica aerogel [2] and in another, equal spin pairing states within nematically oriented alumina hydrate aerogels [3].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…They are just two of many p-wave states each distinguished by unique broken symmetries and these are the only stable states in pure 3 He in low magnetic field [1]. However, new phases in this manifold have been reported for superfluid confined within an anisotropic external framework; in one case chiral states within positively strained 98% porous, silica aerogel [2] and in another, equal spin pairing states within nematically oriented alumina hydrate aerogels [3].…”
mentioning
confidence: 99%
“…It has been shown that the relative stabilities of various superfluid states of 3 He can be influenced by anisotropy in a silica aerogel framework. We prepared a suite of aerogel samples compressed up to 30% for which we performed pulsed NMR on 3 He imbibed within the aerogel.…”
mentioning
confidence: 99%
See 3 more Smart Citations